PERUBAHAN SOSIAL MASYARAKAT DI PERDESAAN HUTAN RAWA GAMBUT (Kajian Alih Guna Hutan Rawa Gambut Menjadi Perkebunan Kelapa Sawit di Kecamatan Marabahan Kabupaten Barito Kuala) - Nurhidayati Nurhidayati; Hafizianor Hafizianor; Muhammad Muhammad; Hamdani Fauzi (EnviroScienteae, 2016)
The purposes of this study are to 1) study the history, process, and factors of the background of the conversion of wetland forests into palm oil plantations, 2) analyze the social changes that occur in the aspect of population (demography), which includes changes in population structure and processes of the population, 3) to analyze the social changes that occur in the socio-economic aspects of forest villagers concerning domestic economic conditions of the society and the contribution of forest resources to the community, 4) analyze the social changes that occur in the socio-cultural aspects of rural community that include the status and social roles, social stratification and social mobility. This research used a quantitative approach with the questionnaires which were analyzed by Wilcoxon Match Pairs, Differential test and quantitative analysis techniques Enumeration. This study was carried out in two villages: Antar Raya and Antar Jaya which are located in Marabahan, Kabupaten Barito Kuala. The results showed that: 1) the history and the process of changing over the peat swamp forests into oil palm plantations began to exist in both places since 2008. The peat boglands were converted into oil palm plantations  which were formerly forests for public rice farming, and looking for Galam wood, rattan, and  fish. The background factors of the function changes were among others: a) the untapped potential of peat swamp forests, so that local governments and entrepreneurs were willing to use the land, b) people who wanted to have more developed and prosperous lives; c) public expectations that the opening of employment opportunities as well as obtaining compensation or redressing land ownerships; 2) changes in society due to the conversion of the peat swamp forests into oil palm plantations, which caused social changes  occur in the aspect of population (demographics); 3) social changes that occurred in the socio-economic aspects, among others: a) the state of the economy of the forest village communities; b) the role of forest resources for the community; 4) social changes that occurred in the socio-cultural aspects, namely a change occurs in status and social role, changes also occurred in the social stratification, and changes also occurred in the social mobility of families.